Results in June - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The survey of 'How Do You Use Spore' closed on 1 February 2002. You can still send your answers to the survey questions (see Spore 95, or ask for them by email from questions-en@spore-magazine.org). However, we cannot include any answers received...